Assessing the impact of microfinance on poverty reduction in the Kumasi Metropolis - Ofosu, Tabiri (2016)
A thesis submitted to The Board of Graduate Studies, Kwame Nkrumah University of Science and Technology, School of Business, in partial fulfillment of the requirements for the award of a Master of Business Administration (Mba Marketing),